Facile Synthesis of Bi2S3@SiO2 Core-Shell Microwires as High-Performance Anode Materials for Lithium-Ion Batteries. Issue 1 (1st January 2017) - Tang, Chunjuan; Li, Narui; Sheng, Jinzhi; Zhou, Liang; He, Liang; Zhu, Jiexin; Li, Feng; Liu, Yuning; Mai, Liqiang
Abstract : Anode materials with high capacity are urgently required to substitute graphite. The theoretical gravimetric and volumetric capacities of Bi2 S3 are much higher than those of graphite, but the cycling performance of Bi2 S3 is poor due to its large volumetric expansion. Amorphous SiO2 is mechanically rigid, which can buffer the volume change. A novel Bi2 S3 @SiO2 core-shell microwire is firstly designed and synthesized in this work. The composite exhibits excellent electrochemical performances. The discharge capacity is 379 mA h g −1 after 4000 cycles at the current density of 1 A g −1 .